2001
DOI: 10.1523/jneurosci.21-23-09134.2001
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dopamine Release Via Presynaptic D2 Receptors: Time Course and Functional CharacteristicsIn Vivo

Abstract: Most neurotransmitters inhibit their own release through autoreceptors. However, the physiological functions of these presynaptic inhibitions are still poorly understood, in part because their time course and functional characteristics have not been described in vivo. Dopamine inhibits its own release through D2 autoreceptors. Here, the part played by autoinhibition in the relationship between impulse flow and dopamine release was studied in vivo in real time. Dopamine release was evoked in the striatum of ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
231
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(258 citation statements)
references
References 44 publications
(108 reference statements)
24
231
2
1
Order By: Relevance
“…It will be interesting to see the extent to which these and other factors participate in vivo. A recent in vivo report using D2 receptor mice finds a similar overall profile of autoinhibition to the present study with a clear onset and offset but slightly shorter peak time (Benoit-Marand et al, 2001b). Considering the methodological differences (in vivo vs. in vitro, D2 knockout mice vs. pharmacological D2 receptor blockade in rats), the findings are encouragingly consonant.…”
Section: Discussionsupporting
confidence: 89%
“…It will be interesting to see the extent to which these and other factors participate in vivo. A recent in vivo report using D2 receptor mice finds a similar overall profile of autoinhibition to the present study with a clear onset and offset but slightly shorter peak time (Benoit-Marand et al, 2001b). Considering the methodological differences (in vivo vs. in vitro, D2 knockout mice vs. pharmacological D2 receptor blockade in rats), the findings are encouragingly consonant.…”
Section: Discussionsupporting
confidence: 89%
“…The absence of an effect of aripiprazole on impulsivity in this study might suggest that inter-individual differences in impulsivity on the 5-CSRT task are not related to major differences in DA release, consistent with evidence that HI rats do not show higher striatal DA release than non-impulsive rats (Dalley et al, 2007). The lower number of DA D2/3 receptors in the ventral striatum of HI rats would hence not seem to be associated with an impairment in presynaptic function, which would directly affect DA tone (Benoit-Marand et al, 2001), but rather to a change in postsynaptic activity. However, previous research has shown that electrically evoked DA release is increased and decreased in the NAcbS and NAcbC, respectively, in HI compared with LI rats (Diergaarde et al, 2008).…”
Section: Dopamine Receptor Modulation Of Impulsivity M Besson Et Alsupporting
confidence: 84%
“…D 2 receptors exert both presynaptic and postsynaptic functions. In their presynaptic autoreceptor function, mediated by the D 2 S isoform, these receptors are responsible for the regulation of DA synthesis and, consequently, impulse-dependent dopamine release (Baik et al, 1995;Missale et al, 1998;Usiello et al, 2000;Benoit-Marand et al, 2001). Postsynaptic D 2 receptors have been associated with, among other effects, stimulation of locomotion and the development of haloperidol-induced catalepsy (Baik et al, 1995;Usiello et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Postsynaptic D 2 receptors have been associated with, among other effects, stimulation of locomotion and the development of haloperidol-induced catalepsy (Baik et al, 1995;Usiello et al, 2000). A loss of D 2 autoreceptor function thus should result in an increase of DA synthesis and, consequently, release (Benoit-Marand et al, 2001), which would in turn lead to a reduction in striatal Akt phosphorylation as demonstrated in DAT-KO and amphetamine-treated WT mice (Beaulieu et al, 2004(Beaulieu et al, , 2005. However, the increased basal Akt phosphorylation in D 2 -KO as well as in D 2 L-KO mice, which do not display major changes in D 2 autoreceptor function (Usiello et al, 2000), indicate that the negative regulation of Akt by DA is mostly a postsynaptic phenomena regulated by D 2 receptors.…”
Section: Discussionmentioning
confidence: 99%